Role of the physician in patient safety in transfusion reactions: an integrative review (Research, Society and Development, 2020)
The transfusion of blood components is a relevant intervention in current therapy. If used properly, it can significantly decrease the mortality rate and improve the health of patients; however, as in other therapeutic care actions, it can lead to complications such as the transmission of infectious microorganisms among other clinical complications. Therefore, the article aims to write the possible transfusion reactions that affect the patient in blood transfusion and the proposal of strategies to reduce the possible transfusion reactions that affect the patient in blood transfusion. As a methodology, it is an integrative review research, which includes the theoretical conceptions of approach, the set of techniques that enable the construction of reality and the divine breath of the researcher's creative potential. Articles published in virtual databases were used. For this purpose, the Virtual Health Library was used, in the LILACS, BDENF, MEDLINE and Google Scholar databases, with a time frame from 2014 to 2018. After reflective reading of the articles, two categories emerged for data analysis and results found. Transfusion medicine is a complex process that depends on a multidisciplinary team, which plays a fundamental role in the safety of blood transfusion and whose responsibility even consists in keeping the patient informed about the procedures to which he is submitted. It is concluded that the practice of hemotherapy is multiprofessional, and therefore, needs competent, responsible professionals with theoretical and scientific knowledge, to ensure the quality and safety of the patient who experiences the transfusion process transcending the health-disease process.